2016
DOI: 10.1124/dmd.116.071373
|View full text |Cite
|
Sign up to set email alerts
|

Early Alterations of Bile Canaliculi Dynamics and the Rho Kinase/Myosin Light Chain Kinase Pathway Are Characteristics of Drug-Induced Intrahepatic Cholestasis

Abstract: Intrahepatic cholestasis represents 20%-40% of drug-induced injuries from which a large proportion remains unpredictable. We aimed to investigate mechanisms underlying drug-induced cholestasis and improve its early detection using human HepaRG cells and a set of 12 cholestatic drugs and six noncholestatic drugs. In this study, we analyzed bile canaliculi dynamics, Rho kinase (ROCK)/myosin light chain kinase (MLCK) pathway implication, efflux inhibition of taurocholate [a predominant bile salt export pump (BSEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 66 publications
(67 reference statements)
10
46
0
Order By: Relevance
“…BC formed in HepaRG cell cultures appear as characteristic refractive structures, corresponding to bright/white objects on phase-contrast photographs, as previously reported 21 , whereas cells appear as dense/black elements, containing nuclei recognizable by their round/delimited shape and differential density. After capturing images using an Axiovert 40 C phase contrast microscope (Carl Zeiss, Le Pecq, France) and adjusting brightness parameters to optimally distinguish between white and black densities, bright objects reflecting BC as well as round/delimited nuclei-related objects were segmented by adjusting the shape and area parameters to exclude non-corresponding objects, using a dedicated in-house macro-program based on ImageJ 1.48 software 22 .…”
Section: Methodssupporting
confidence: 80%
“…BC formed in HepaRG cell cultures appear as characteristic refractive structures, corresponding to bright/white objects on phase-contrast photographs, as previously reported 21 , whereas cells appear as dense/black elements, containing nuclei recognizable by their round/delimited shape and differential density. After capturing images using an Axiovert 40 C phase contrast microscope (Carl Zeiss, Le Pecq, France) and adjusting brightness parameters to optimally distinguish between white and black densities, bright objects reflecting BC as well as round/delimited nuclei-related objects were segmented by adjusting the shape and area parameters to exclude non-corresponding objects, using a dedicated in-house macro-program based on ImageJ 1.48 software 22 .…”
Section: Methodssupporting
confidence: 80%
“…Disruption of BC dynamics by certain drugs is associated with occurrence of cholestasis injury 24 . If few cholestatic drugs such as cyclosporine A 31, 32 and chlorpromazine 33 , induced constriction of BC associated with irreversible severe damage and cell death, others covering a wider range of cholestatic compounds, induced dilatation 24, 34 . Importantly, BC dilatation is observed in patients suffering from cholestasis 35, 36 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to drug-mediated inhibition of hepatocellular transport function, the inter-individual variability of transporter expression and function are altered by pre-existing hepatic diseases and genetic factors, which are believed to contribute to the development of drug-induced risk of cholestasis in susceptible individuals (Trauner et al, 1998). Recently, some of us reported that cholestatic drugs caused alteration of bile canaliculi dynamics associated with impairment of the Rhokinase/ myosin light chain kinase signaling pathway using human HepaRG cells (Burbank et al, 2016;Sharanek et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A validation of the model was further achieved by use of two prototypical cholestatic drugs, cyclosporine A (CsA) and chlorpromazine (CPZ), previously shown to exhibit differences in the mechanisms of apical and basolateral transporter inhibition (Antherieu et al, 2013;Sharanek et al, 2014) and their effect on BC dynamics (Burbank, et al 2016).…”
Section: Introductionmentioning
confidence: 99%